Evaluation of prevulcanisate relaxed modulus of prevulcanised natural rubber latex using Fourier transform near infrared spectroscopy - Lim, Chin Hock; Sirisomboon, Panmanas (My University, 2017)
The analysis of the cross-link density of prevulcanised natural rubber latex using near infrared spectroscopy was conducted using a Fourier transform near infrared spectrometer in diffuse reflection mode over the wavenumber range of 12500- 3600 cm-1. As the density of cross-link is an indication of the degree of cure, hence the properties of the latex products, the proposed method is useful for industrial purposes. For samples of prevulcanised latex of 50% total solids content (i.e. PV 50%) at 100% extension (prevulcanisate relaxed modulus 100%), the best model was developed using the partial least squares regression from the spectra, which were pre-treated using the first derivative method, where the coefficient of determination (r2), root mean square error of prediction and bias were 0.66, 6.06×104 Nm-2 and 1.63×104 Nm-2, respectively. The ratio of standard error of prediction to the standard deviation of the reference data in the prediction sample set was 1.8. This model could be used for screening. For samples at 300% extension (prevulcanisate relaxed modulus 300%) for PV 50%, the best model was developed using spectra pre-treated for scattering correction: r2, root mean square error of prediction and bias were 0.88, 6.74×104 Nm-2 and 1.35×104 Nm-2, respectively and the ratio of prediction to deviation was 3.0. Hence, the near infrared spectroscopy technique can be utilised as a rapid screening method for estimating the cross-link densities of prevulcanised natural rubber latex.
Keywords: Cross-link density; Near infrared spectroscopy; Partial least squares regression; Prevulcanisate relaxed modulus; Prevulcanised latex